(untitled) (Journal of School Administration Research and Development, 2021)
This case study explored how a principal in a suburban elementary school in the northeastern United States empowered students and used student voice to develop his own leadership. The researchers collected and analyzed data in the form of observations, principal interviews, and student focus groups. Results and discussion describe and explain how the principal engaged with students’ perspectives to structure his experiences of school and learn- ing. Also, results indicate that the principal’s self- awareness of his instructional leadership actions, particularly regarding the inclusion of student voice and agency, is critical for effective and meaningful leadership. This case provides a new direction for develop- ing and practicing school leaders to consider self- evaluation, and reflection as part of ongoing leadership improvement, framed by the research-based concepts of instructional leadership, student voice, and perceptual congruence. Finally, the case study provides an opportunity for the field of educational research to open meaningful and often-overlooked discussions emphasizing the value of including students in models of shared instructional leadership and empowering youth as learners and leaders in their own right.